PERAN BAHASA DAERAH DALAM RITUAL ADAT DAN TRADISI LISAN DESA LEMBUR TIMUR KECAMATAN LEMBUR KABUPATEN ALOR - Enjel Maryana Weni; Elsa Miranda Lanmai, Esriyanti Lakapada, Endang Serang , Halena Muna Bekata, ElsaNoza Puling, Petrus (CV. ADIBA AISHA AMIRA, 2025)
This study aims to examine the role of local languages, especially East Lembur local languages, in traditional rituals and oral traditions that develop in East Lembur Village, Lembur District, Alor Regency. In this community, local language is not only a means of daily communication, but also as a means of connecting with ancestors, a symbol of cultural identity, and as a medium that maintains customs. This research uses a qualitative approach with ethnographic approach methods, interviews and observations of the implementation of traditional rituals and oral traditions in the village. The results showed that local languages have a central role in expressing cultural values, strengthening social ties, and supporting the continuity of traditional rituals in the village of lembur timur.